2023
DOI: 10.1097/sap.0000000000003667
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Acellular Dermal Matrix–Based Breast Reconstruction in Previously Irradiated Breasts

Andrea Lisa,
Riccardo Carbonaro,
Manuela Bottoni
et al.

Abstract: Radiation therapy is considered today an integral part of the management of breast cancer. However, radiotherapy significantly increases the incidence of total complications in breast reconstruction. Several procedures have been adopted to reduce complication rates in irradiated fields, including the use of acellular dermal matrices (ADMs). We conducted a retrospective analysis of our single-center experience with ADM-assisted implant-based reconstruction or revision surgeries for capsular contracture treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The cause of such different results is unclear. Some authors [2,13,[33][34][35][36][37] suggest that most of the studies conducted on the effect of an ADM in the postoperative results were made with AlloDerm ® , which is a product that has been sold for longer, and only more recently, a series has been published with the use of other ADM, both from human and porcine origin, and although the preparation is similar in removing the cellularity of the tissue and infectious organisms, there may be subtle unpublished differences in the processing and storage of these products, causing an inflammatory response with a higher influence in the formation of seroma that could also be related to the increase in other complications such as infections or extrusions of the implant [34]. Reference is also made to important immunological differences between the matrices of human or non-human origin that can influence the rate of complications, preventing extrapolation of results from different studies [14,35,[38][39][40].…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…The cause of such different results is unclear. Some authors [2,13,[33][34][35][36][37] suggest that most of the studies conducted on the effect of an ADM in the postoperative results were made with AlloDerm ® , which is a product that has been sold for longer, and only more recently, a series has been published with the use of other ADM, both from human and porcine origin, and although the preparation is similar in removing the cellularity of the tissue and infectious organisms, there may be subtle unpublished differences in the processing and storage of these products, causing an inflammatory response with a higher influence in the formation of seroma that could also be related to the increase in other complications such as infections or extrusions of the implant [34]. Reference is also made to important immunological differences between the matrices of human or non-human origin that can influence the rate of complications, preventing extrapolation of results from different studies [14,35,[38][39][40].…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“… 17 In other studies, the incidence of capsular contracture (Baker III/IV) ranged from 3.2% to 13.6%, which is lower compared with reported rates for submuscular IBR without ADM. 13 , 34 Lisa et al recently reported encouraging results concerning ADM-assisted revision surgery in irradiated breasts to prevent capsular contracture. 37 …”
Section: Discussionmentioning
confidence: 99%
“…17 In other studies, the incidence of capsular contracture (Baker III/IV) ranged from 3.2% to 13.6%, which is lower compared with reported rates for submuscular IBR without ADM. 13,34 Lisa et al recently reported encouraging results concerning ADM-assisted revision surgery in irradiated breasts to prevent capsular contracture. 37 RBS is characterized by transient cutaneous erythema over the ADM and is a well-known reaction associated with a reported incidence reaching up to 27%. 38 In our study, "breast redness" (41.1%) included both RBS and suspected or confirmed infections.…”
Section: Discussionmentioning
confidence: 99%